What motivates entrepreneurs? A study of the value systems of Filipino entrepreneur - Uy, Arnel Onesimo O. (Animo Repository, 2011)
Given the pivotal role of the entrepreneur in nation building and economic development, the key to unleashing his full potential for economic growth is to identify and understand his values and value system which affects his attitude and subsequently his behavior. While there are studies on what are the character traits of Filipino entrepreneur, a few have explored the personal value system that affects these attributes and characteristic traits. This study identified the value system of Filipino entrepreneurs using the universally accepted Rokeach Value Survey (RVS) and in the process provided an explanation to underlying the findings of other studies about the characteristics and styles of Filipino entrepreneurs following the VALUESATTITUDE- BEHAVIOR framework. Furthermore, the study tested whether the value systems are homogeneous and concludes by discussing the implications to economic policies of the country.